Heme-Dependent ER Stress Apoptosis: A Mechanism for the Selective Toxicity of the Dihydroartemisinin, NSC735847, in Colorectal Cancer Cells - Elhassanny, Ahmed E. M.; Soliman, Eman; Marie, Mona; McGuire, Paul; Gul, Waseem; ElSohly, Mahmoud; Van Dross, Rukiyah (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is a leading cause of cancer death in the United States. Artemisinin derivatives, including the dihydroartemisinin (DHA) monomers, are widely used as clinical agents for the treatment of malaria. Numerous studies demonstrate that these molecules also display antineoplastic activity with minimal toxicity. Of interest, dimeric DHA molecules are more active than their corresponding monomeric ones. Our previous data showed that the DHA dimer, NSC735847, was a potent inducer of death in different cancer cell types. However, the mechanism of action and activity of NSC735847 in colon cancer cells was not explored. The present study investigated the anticancer activity of NSC735847 and four structurally similar analogs in human tumorigenic (HT-29 and HCT-116) and non-tumorigenic (FHC) colon cell lines. NSC735847 was more cytotoxic towards tumorigenic than non-tumorigenic cells. In addition, NSC735847 exhibited greater cytotoxicity and tumor selectivity than the NSC735847 derivatives. To gain insight into mechanisms of NSC735847 activity, the requirement for endoplasmic reticulum (ER) stress and oxidative stress was tested. The data show that ER stress played a key role in the cytotoxicity of NSC735847 while oxidative stress had little impact on cell fate. In addition, it was observed that the cytotoxic activity of NSC735847 required the presence of heme, but not iron. The activity of NSC735847 was then compared to clinically utilized CRC therapeutics. NSC735847 was more effective in killing colon cancer cells than oxaliplatin (OX). In addition, greater cytotoxicity was observed in colon cancer cells that were co-treated with folinic acid (Fol), 5-FU (F), and NSC735847 (FolFNSC), than with Fol, F, and OX (FolFOX). The selective activity of NSC735847 and its ability to increase the cytotoxicity of clinically utilized CRC antineoplastics suggest that NSC735847 may be an effective agent for treating colon cancer.